Analisis Peran dan Tanggung Jawab Perusahaan terhadap Para Investor Pasar Modal Indonesia - Angelina Sidiprasetija; Celia Angelyn Coandi (Jurnal Hukum Lex Generalis, 2024)
Many people invest in Indonesia's capital market, requiring companies to protect investors and ensure transparency. This research examines corporate roles in mandatory information disclosure and investor protection under Company and Capital Market Law. Investors face risks like insider trading, market manipulation, and contract breaches, making transparency in financial and operational reporting essential. The Financial Services Authority (OJK) supervises the capital market, influencing investor confidence and market stability. Using a normative juridical method, this study finds that transparency and accountability boost investor trust, impacting market liquidity and company value. Despite the legal protections, challenges and risks in the capital market remain.